From threat to opportunity: Gaming the algorithmic system as a service - Marijn Sax; Hao Wang (Internet Policy Review, 2025)
Gaming the system - i.e., strategic attempts to manipulate the input(s) for, or one's interactions with, an algorithmic system to try to secure a better outcome than intended by the system's design - is commonly portrayed as a threat to online platforms and services. Tech companies often use this gaming concern to justify their reluctance to provide algorithmic transparency. In this paper, however, we will explore a new business model in the digital economy we call gaming-the-system-as-a-service (GaaS). In this model, transparency promises are wrapped into an assisted gaming service and sold as a premium feature. This way, the alleged risk of transparency - gaming the system - is turned into a monetisation feature for service providers. As such, GaaS is a typical example of how tech companies can attempt to turn regulatory pressures (e.g., to provide more insight into how its algorithmic curation and recommendation systems work) into a commercial opportunity. To begin to rethink our normative and regulatory approaches to the interface of transparency and gaming, we perform a first exploration of several potential challenges posed by this new business model. First, GaaS is entwined with an incentive structure that is hostile to consumers and exploitative in nature. Second, GaaS is essentially a pay-to-win feature, raising questions of equality and fairness. Third, the commodification of transparency through GaaS can 'taint' and erode transparency as an important democratic value.
Keywords: 300; Gaming; Algorithmic transparency; Ethics; Manipulation; Algorithmic decision-making